AYO MURUP (AYO MENGUBAH LIMBAH JADI RUPIAH): PELATIHAN MENGOLAH LIMBAH MINYAK JELANTAH MENJADI LILIN UNTUK WALI MURID TK NEGERI 2 YOGYAKARTA - Nursih, Bestari; Widyastuti, Niken; Septianna, Ratih; Fatimah, Siti; Kamilani, Anis Khamdan (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
The AYO MURUP (Let's Change Waste into Rupiah) program is a training activity for processing used cooking oil waste into candles, aimed at parents of students of TK Negeri 2 Yogyakarta. This activity aims to increase environmental awareness and provide practical skills that have economic value for the community. Used cooking oil, which has been considered household waste, can actually be reused into useful products, such as aromatherapy candles and multipurpose candles. The training was carried out through a participatory approach, where participants were actively involved in the candle-making process, from collecting materials, processing, to product packaging. The results of this training showed an increase in participants' knowledge and skills in managing used cooking oil waste. This program is expected to have a broad impact on environmental education and community empowerment activities.